1984
DOI: 10.1152/ajprenal.1984.247.5.f837
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for electroneutral chloride transport in rabbit renal cortical brush border membrane vesicles

Abstract: Controversial evidence exists as to whether electroneutral Cl-OH exchange occurs across the proximal tubular brush border membrane of the mammalian kidney. To help resolve this controversy, we carried out a series of experiments using rabbit renal cortical brush border membrane vesicles to determine the effect of changes in pH on 36Cl uptake across this membrane. Reducing pH equally inside and outside of the vesicle stimulated Cl-Cl exchange as well as chloride uptake. A proton gradient (out greater than in) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…There have been previous proposals for the existence of Cl--OH-exchange in cell membranes. These have been specifically for epithelial membranes, and are based solely on radiolabelled Cl-flux studies in vesicles prepared from brush-border membranes of rabbit renal cortex (Shiuan & Weinstein, 1984) and rabbit ileum (Fan, Faust & Powell, 1983), and from apical membranes of rat distal colon (Rajendran & Binder, 1993). Interestingly, this last report suggests the co-existence of an AE and a CHE carrier, although there is no evidence for the effect of these carriers on pH,.…”
Section: Discussionmentioning
confidence: 99%
“…There have been previous proposals for the existence of Cl--OH-exchange in cell membranes. These have been specifically for epithelial membranes, and are based solely on radiolabelled Cl-flux studies in vesicles prepared from brush-border membranes of rabbit renal cortex (Shiuan & Weinstein, 1984) and rabbit ileum (Fan, Faust & Powell, 1983), and from apical membranes of rat distal colon (Rajendran & Binder, 1993). Interestingly, this last report suggests the co-existence of an AE and a CHE carrier, although there is no evidence for the effect of these carriers on pH,.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies in isolated apical membrane vesicles have disagreed with respect to the presence or absence of C1/OH exchange (9)(10)(11)(12)(13)(14)(15). Karniski and Aronson (16) found rapid Cl/formate exchange in these apical membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Warnock and Yee (2) first demonstrated an electroneutral Cl-/base exchanger in brush border vesicles. Subsequent vesicle studies either confirmed (3)(4)(5) or failed to obtain (6-9) similar results. In contrast to the apical membrane, the presence of Na+-independent Cl-/base exchange in basolateral membrane vesicles (10)(11)(12) and whole tubule studies (13)(14)(15)(16)(17) is less controversial.…”
Section: Introductionmentioning
confidence: 99%